The Protestant Ethic and the Spirit of Facebook: Updating Identity Economics. (April 2020) - Lim, Elisha
Scholars and news media generally name Facebook's two central problems: that its data collection practices are a threat to user privacy, and that stricter regulations are required to prevent "bad actor" from spreading hate and disinformation. However separating these two concerns—personal data collection and bad actors—overlooks the way that one generates the other. First, this article builds on critical race scholarship to examine how identity politics are historically distorted and commodified into profitable vigilance and intolerance, in what I call a transition from identity politics, to personal identity economics . Facebook's Ad Manager, for example, reveals how personal identities are itemized as advertising assets, which are cultivated through deeper, more trenchant identity politics. Second, this article theorizes about what makes such staunch, intolerant identity politics addictive. Drawing on Max Weber's theories of the Protestant Ethic, this article explores how Facebook activism thrives on deep-rooted Christian paradigms of dogma, virtue, redemption, and piety. As dogmatic personal identity economics spread across the globe, they testify to how Facebook's business model manufactures bad actors.